Aktor Non-Negara dalam Hubungan Internasional: Studi Kasus Detox Campaign oleh Greenpeace di Republik Rakyat Tiongkok - Trianda, Farin; Wahyudi, Fendy Eko; Pattipelohy, Shary Charlotte (Journal of International Relations, 2018)
Environmental issue in China is a concern for international relations actors, including nonstateactors. Greenpeace is an international non-government organization that acts to solveglobal environmental problems in China. This research will explain an environmentalcampaign, Detox Campaign, by Greenpeace to solve water pollution problem in China.This research aims to explain challenges that Greenpeace has faced in conducting DetoxCampaign in China. In conducting Detox Campaign, Greenpeace has faced challenges thatcontribute to Greenpeace’s failure to change China’s government policy. This researchused Global civil society as a theoretical framework, to explain external factors aschallenges for Greenpeace in conducting Detox Campaign in China. This research foundthat water pollution issue is not a main priority in China and Greenpeace is stillconstrained by their limited organizational capacity. Greenpeace has limited political spacein terms of policy advocacy that caused failure of Detox Campaign in China.